Tafsir Al-Qur’an Al-Majid“Al-Nur” Karya T.M.Hasbi Ash- Shiddieqy (Corak Tafsir berdasarkan Perkembangan Kebudayaan Islam Nusantara) - Andi Miswar (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2015)
Tafsir al-Qur’an al-Majid “al-Nur” is a work by T.M.Hasbi Al-Siddieqy, by applying tahlili writing method with tafsir fiqh characteristic, this work is present to meet the demands of Islamic culture development in Indonesia. With Indonesia nuanced interpretation (tafsir) provides convenience for those who do not understand Arabic well, so it can lead Indonesian people practicing the Qur'an and the Hadith, for the development of religion and nation.